Sweetpotato action for security and health in Africa (SASHA) phase II. Project profile. - International Potato Center (International Potato Center, 2019)
Sweetpotato is a nutritious and resilient crop. This project builds on earlier work by the International Potato Center (CIP) to tackle the bottlenecks in sweetpotato consumption and delivery to release its economic and nutritional potential in rural Africa and improve nutrition. SASHA II focuses on developing breeding approaches and locallyadapted varieties, building sustainable seed systems and improved storage methods, promoting vitamin A rich varieties and their use as purée in processing as well as supporting the growth of a dynamic community of practice in the four technical areas.